STRATEGI PERENCANAAN MITIGASI BENCANA KEBAKARAN HUTAN DAN LAHAN DI DESA CINTA JAYA, KABUPATEN OGAN KOMERING ILIR TAHUN 2022 (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2023)
Forest and land fires are a disaster that often occurs. If it is not handled in an appropriate and effective way, the number of cases of forest fires in the world will continue to increase. The impact of forest and land fires is very dangerous and detrimental both from the economic, social, ecological and health aspects. The purpose of this research is to formulate an appropriate and effective forest fire disaster mitigation strategy. This research method uses descriptive with a qualitative approach. Data collection techniques are carried out by observation, interviews, and documentation. The data were taken from sources that were determined based on the purposive sampling technique. This study used three components, namely: Prevention, Management, and Post-Disaster.